Simultaneous determination of estrone and selected pesticides in water medium by GC-MS after multivariate optimization of microextraction strategy - Bulgurcuoglu, Ayse Evrim; Yilmaz, Busra; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2018)
A sensitive and accurate analytical method based on dispersive liquid-liquid microextraction was developed for the simultaneous determination of selected pesticides, hormones, and endocrine disruptors by GC-MS. The optimum conditions of the extraction procedure were determined using an experimental design of factors significantly affecting the extraction output. Analysis of variance (ANOVA) was used to evaluate the main effects of experimental factors and their interactions. The limit of detection values determined for the analytes under optimum experimental conditions were found to be between 0.30-2.0 ng/mL. The linear calibration plot of analytes span across a wide concentration range and low %RSD values from replicate measurements indicated good precision of the developed method. Spiked recovery tests were also performed on municipal wastewater, well water, lake water, sea water, and tap water matrices to determine the method's accuracy and applicability to water samples. The recovery results obtained were satisfactory for all water samples.
Keywords: Dispersive liquid-liquid microextraction; Factorial design; Multivariate optimization; Pesticides; Endocrine disruptors; Hormones; LIQUID-LIQUID MICROEXTRACTION; RESIDUES; QUECHERS; CANCER; FUNGICIDE; SAMPLES; Environmental Sciences & Ecology